Rotational/compressional nature of the magnetopause: Application of the BV technique on a magnetopause case study. Issue 3 (25th March 2014) - Dorville, Nicolas; Belmont, Gérard; Rezeau, Laurence; Grappin, Roland; Retinò, Alessandro
<x xml:space="preserve">Abstract</x> The magnetopause boundary implies two main kinds of variations: a density/temperature gradient and a magnetic field rotation. Other variations are associated with these two, concerning in particular the flow velocity, the electric field, and the plasma composition. Compressional and rotational variations are always observed in a close vicinity of each other, if not inseparably mixed. We present a case study from the Cluster data where the two are clearly separated and investigate the natures of both layers, using the new "BV" method for discontinuity analysis. We evidence that the first one is a slow shock while the second is a rotational discontinuity. The interaction between these two kinds of discontinuities is then studied with the help of 1.5‐D magnetohydrodynamics simulations. The comparison with the data is quite positive and, associated with general theoretical arguments, leads to think that most of the generic properties of the magnetopause may be interpreted in this sense. Our results suggest that a "shaken" magnetopause is made of the sum of several discontinuities: slow shocks and rotational discontinuities. A statistical study on a larger set of data will be necessary to check this conjecture.